PERANCANGAN KAWASAN MIX-USED DENGAN PENDEKATAN TRANSIT ORIENTED DEVELOPMENT (TOD) DI PEKANBARU - Ratna Dilla Sukma (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2020)
Pekanbaru is a city with the most populous population in Riau Province by touching 1,064,566 people in 2016 (BPS, 2017). In addition, based on data from BPS Kota Pekanbaru (2015), Pekanbaru City is the largest density’s city of motor vehicles in Riau Province with a total of 10,594.1 vehicles, this is one of the factors causing sprawl in Pekanbaru City. In addition, factors of population growth, urban sprawl, and consumptive community behavior have an impact on increasing mobility in travel rates, travel distances and vehicle travel times. The design of Transit Oriented Development (TOD) refers to the development of the integrity of transit with Mix-usedarea, and adjusting existing land use to reduce some of the problems that exist in urban areas. The concept strategy used to prioritize factors of connectivity, density, and mix in Pekanbaru BRPS Terminal area which is a transition point for public transportation mode of Pekanbaru, to management the land use, and the integration of supporting all activities in the area.